Incorrect Knowledge of Event-Driven PrEP "2-1-1" Dosing Regimen Among PrEP-Experienced Gay and Bisexual Men in Australia. (1st June 2022) - Chan, Curtis; Vaccher, Stefanie; Fraser, Doug; Grulich, Andrew E.; Holt, Martin; Zablotska-Manos, Iryna; Prestage, Garrett P.; Bavinton, Benjamin R.
Abstract : Background: Event-driven pre-exposure prophylaxis (ED-PrEP), when taken according to the "2-1-1" dosing method, is highly effective at preventing HIV acquisition for gay, bisexual, and other men who have sex with men (GBM). Any missed doses when using ED-PrEP drastically reduce its effectiveness, so it is vital that people using this method know how to take it correctly. This study investigated Australian GBM's awareness of ED-PrEP and their knowledge of how to take it correctly. Method: We conducted a survey of 1471 PrEP-experienced GBM in Australia, between October 2019 and March 2020. The survey assessed awareness and knowledge of the 3 components of the "2-1-1" ED-PrEP dosing regimen (number of pills for loading dose, timing of loading dose, and number of days after sex to take PrEP pills) among GBM. Characteristics associated with ED-PrEP awareness and correct knowledge of how to take ED-PrEP were assessed with multivariate logistic regression. Results: Two-thirds (n = 1004, 68.4%) had heard of ED-PrEP, of whom only one-eighth (n = 125, 12.5%) knew the correct details of the "2-1-1" ED-PrEP method; one-third (n = 339, 33.8%) did not know any of the 3 key components. Awareness of ED-PrEP and correct knowledge was associated with greater belief in PrEP efficacy, university education, and intention to take a nondaily PrEP regimen in the next 6 months. Conclusions: Although ED-PrEP awareness was considerable, most participants did not know how to use ED-PrEP correctly. Further work is needed to increase awareness and knowledge of ED-PrEP among GBM.